Two Directional Olefinic-Ester Ring-Closing Metathesis using Reduced Ti Alkylidenes. A Rapid Entry into Polycyclic Ether Skeletons - Zhang, Yuan (2009)
[Image: see text] The use of a reduced titanium ethylidene reagent in an efficient 2-directional approach to polycyclic ether skeletons is described.